God's Transforming Spirit: Reflections on Mission, Spirituality and Creation (International review of mission, 2012)
God's transforming Spirit takes us where theology matters most: how we speak of the life of God in a way that speaks to the life of the world. The following reflections undertake this especially in the context of the pre-eminent crisis in the world's life today, the pollution and unrepentant exploitation of the earth. In some senses, these reflections flow from an environmental liberation theology, trying to address issues of creation, mission and spirituality from the perspective of earth's hurt and her Creator's pain. They even aim to come from a new “below”, lifting up the complex, diverse non-human life of the planet to be understood as partner and agent in God's mission. Informed by injustices of human exploitation of the earth, this study is, nevertheless, inspired by hope in the earth's Creator, Redeemer and Sustainer. While rooted in a deeply trinitarian notion of God, it sees a new and exciting route into these issues via the particular life of the Trinity expressed in the ru'ach Spirit. There is a wide spectrum of terms for the Spirit. This document allies itself with an eco-feminist perspective on the Spirit as ru'ach. This signals an identification with the eco-feminist perspective as an essential corrective to the androcentric perspective that has been so exploitative. It also opens the way to invite fresh insights from Indigenous Peoples that also inform the characterization of the Spirit in this text. But the fundamental character of the Spirit in this text is transformational. This makes the Spirit dynamic within and beyond Creation and with and without humanity. This dynamic is often recognized in the text as a spiral. This describes the Spirit's movement and is also a metaphor for the spirit as life. “The ru'ach is a force for life, a sign of God's deep compassion embracing all life. Such love calls forth more love in answer and response. We meet her compassion with our care and commitment and find ourselves accountable to each other. The flow of love spirals forth and the gift of life is renewed and transformed”. And further: “This spiralling life force relates, gathers, empowers and sends us into relationship, into gathering, into empowerment as the means by which we witness that all are related, all Connected within Creation and between Creation and Creator”. God's transforming Spirit not only creates and empowers life in general, she also agitates and ferments life into partnership with God's mission. This is the further transformation she brings. She is not a deist Spirit, content to let individual lives exist in isolation but embroils herself in Creation's life, inviting fresh communities turned towards the vision of life she exudes. This study offers a spirituality and praxis for mission that seeks to live in harness with this. Thus there is a balance to be found and sustained that honours Creation and Creator by nurturing justice, peace and love with all our neighbours and our Mother. This re-balance is the mandate given to us by the widow, orphan and stranger, who together with the ru'ach empower this seeking for and celebrating of justice. It is no surprise that the ru'ach Spirit commissions both the Divine Christ (Luke 4:18; see also his baptism: Luke 4:1), the ancient prophets (Isa. 61: 1; Ez. 2:2) and surely those new prophets who rise up generation by generation within and beyond our churches. This vision of a community for and of the earth that exists within and beyond our churches is also crucial to this study. The transformation promised by the ru'ach gathers together people of faith and people who profess no faith, and initiates relationships that our theologies and ecclesiologies need to acknowledge and accommodate. But even this broad notion of fresh community is expanded in these reflections. “We need a companionable anthropology that sees humanity in community with all the other forms of life that show us the means to inhabit the complex whole that the ru'ach breathes into life”. Seeking this mutuality with all life, with all species, is integral to God's mission. Only all together do we embody and honour the divine vision of Creation continuing, and only all together can we respond to God's calling for Creation to continue unfolding. This companionable anthropology invites us to share with the many communities of life that fill the earth, expanding our notion of the “sacred strangers” the ru'ach sends us with love. This is then to understand the mission of God in a new way as incorporating the partnership and agency of all Creation, not just humanity. The study also reflects upon the church, inspired by the ru'ach, as it follows Christ and seeks to be a faithful partner in this mission, prompted by it, not proscribing it. The note of confession and conversion is sounded strongly, as well as the expectation that our values and vision can contribute to the shaping of new lifestyles that bless rather than pollute the earth, that honour the Spirit's gift rather than scorn it and the giver. Thus this exploration concludes that mission, spirituality and Creation must be seen together. The Spirit that sustains Creation sends creatures into mission. Therefore, we are called to participate in God's mission beyond our anthropocentric goals. God's mission is to all of life, and we need to discover new ways of mission that express our reconciled relationship with all created life. We cannot claim that humanity alone will be saved when we see that all of Creation's life is so intentionally interrelated. God's saving love is poured out on all Creation, not on humanity alone. God's love does not proclaim an impending salvation from the earth, but invites our healing and earth's healing through participation in the ru'ach's life. The earth is not to be discarded once our souls are saved, but is also to be transformed through the ru'ach's grace. As the vision of Isaiah and John's revelation tell us, heaven and earth will be made new (Isa. 11: 1–9, cf 25: 6–10, cf. 66:22; Rev. 21: 1–4). Creation's life and God's life are entwined, and God's mission encompasses us all in an ever-giving act of grace and transformation. Peter CRUCHLEY-JONES